2020
DOI: 10.21203/rs.3.rs-21256/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

IFI6 depletion inhibits esophageal squamous cell carcinoma progression through reactive oxygen species accumulation via mitochondrial dysfunction and endoplasmic reticulum stress

Abstract: Background: Esophageal squamous cell carcinoma (ESCC) is one of the most lethal forms of adult cancer with poor prognosis. Substantial evidence indicates that reactive oxygen species (ROS) are important modulators of aggressive cancer behavior. However, the mechanism by which ESCC cells integrate redox signals to modulate carcinoma progression remains elusive. Methods: The expression of interferon alpha inducible protein 6 (IFI6) in clinical ESCC tissues and cell lines was detected by RT-PCR and Western blotti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…RGN has been shown to have antioxidant properties by its activity reducing the production of reactive oxygen species and increasing the antioxidant defenses [ 115 ]. IFI6 depletion suppresses proliferation and induces apoptosis by increasing ROS accumulation, suggesting that IFI6 inhibits ROS accumulation [ 116 ]. Mitochondrial peptidase IMMP2L mutation causes early onset of age-associated disorders and impairs adult stem cell self-renewal [ 117 ], suggesting that IMMP2L inhibits ROS generation.…”
Section: Resultsmentioning
confidence: 99%
“…RGN has been shown to have antioxidant properties by its activity reducing the production of reactive oxygen species and increasing the antioxidant defenses [ 115 ]. IFI6 depletion suppresses proliferation and induces apoptosis by increasing ROS accumulation, suggesting that IFI6 inhibits ROS accumulation [ 116 ]. Mitochondrial peptidase IMMP2L mutation causes early onset of age-associated disorders and impairs adult stem cell self-renewal [ 117 ], suggesting that IMMP2L inhibits ROS generation.…”
Section: Resultsmentioning
confidence: 99%
“…5B and table S9). In two of the three patients we identified a cluster of genes upregulated in both co-culture conditions including MUC5AC , IFI6 and 27, SerpinA1 and LYPD8 , which were previously reported to be involved in tumor progression and metastasis, tumor cell proliferation and poor patient prognosis ( 47–49 ). In the ENAS condition we found upregulation of NMU, EREG and SNHG12 genes.…”
Section: Resultsmentioning
confidence: 84%
“…Downregulation of IFI6 could inhibit ESCC progression through ROS accumulation. 21) To determine whether IFI6 activated p38MAPK signaling pathway was elicited by ROS, we measured the ROS level in HCT116/OXA cells (treated with 4 µM OXA) and found that IFI6 knockdown displayed an enhanced ROS level in cells (Figs. 6A, B).…”
Section: Characterization Of Oxa-resistant Crc Cellsmentioning
confidence: 99%
“…20) In fact, IFI6 is considered as a factor that can promote proliferation and anti-apoptosis in previous reported studies. 19,21,22) Importantly, both in vitro and in vivo results have displayed that chemotherapeutic drugs often activate the apoptosis pathway, thereby promoting their cytotoxicity and inhibiting tumor growth. 23) Therefore, we wondered that if IFI6 was involved in regulating chemoresistance of CRC cells.…”
Section: Introductionmentioning
confidence: 99%